INFLUENCE OF FUSION MIXTURE AND ITS TEMPERATURE ON THE VOLUME OF REWORK STEEL OF TYPE St45L - I. G. Sapchenko; O. N. Komarov; S. G. Zhilin (Литьë и металлургия)
It is determined that the working out technology will allow to increase the using of wastes, to reduce consumption of liquid steel for production of castings, to eliminate defect at casting and etc.